Assessment of frozen ground organic carbon pool on the Qinghai-Tibet Plateau - Jiang, Lin; Chen, Huai; Zhu, Qiuan; Yang, Yanzheng; Li, Mingxu; Peng, Changhui; Zhu, Dan; He, Yixin (Journal of Soils and Sediments, 2019)
PurposeUnder rapid climate change, soil organic carbon (SOC) dynamic in frozen ground may significantly influence terrestrial carbon cycles. The aim of this study was to investigate the storage, spatial patterns, and influencing factors of SOC in frozen ground on the Qinghai-Tibet Plateau, which known as the earth's Third Pole.Materials and methodsUsing the observed edaphic data from China's Second National Soil Survey, we estimated the SOC storage (SOCS) of frozen ground (including permafrost, seasonally, and short time frozen ground) on the plateau with a depth of 0-3m. Furthermore, the effect of vegetation and climate factors on spatial variance of SOC density (SOCD) was analyzed.Results and discussionThe SOCD decreased from the southeastern to the northwestern part of the plateau, and increased with shorten of freezing duration. SOCS of permafrost, seasonally, and short time frozen ground were calculated as 40.9 (34.2-47.6), 26.7 (24.1-29.4), and 6 (5.6-6.4)Pg, making a total of 73.6 (63.9-83.3)Pg in 0-3m depth on the plateau. Normalized difference vegetation index and mean annual precipitation could significantly affect the spatial distribution of SOC in permafrost and seasonally frozen ground.ConclusionsThe soil in plateau frozen ground contained substantial organic carbon, which could be affected by plant and climate variables. However, the heterogeneous landform may make the fate of carbon more complicated in the future.